STUDI KOMPARASI PENERAPAN METODE TRADISIONAL DAN ACTIVITY BASED COSTING UNTUK MENGETAHUI TINGKAT AKURASI PERHITUNGAN HARGA POKOK PRODUKSI (Studi Kasus pada PT. Sinar Bangun Mandiri Kupang) - Bibiana Nona Lilianti Gela; Suryaningsi (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
This study aims to determine the comparison between traditional methods and Activity based costing methods in determining Cost of Production. This research is a qualitative descriptive study conducted at PT. Sinar Bangun Mandiri Kupang. Data collection methods used in this study were documentation and interviews. The research object in this study is data related to determining the cost of production. The results showed that determining the cost of goods manufactured using the activity based costing method gave greater results when compared to using traditional methods. The difference that occurs is due to the imposition of overhead costs on each product, where if using the traditional method the overhead costs are only charged to one cost driver, namely the number of production units, while the Activity-Based Costing System charges the overhead costs for each product is charged to several cost driver so that the Activity Based Costing System is able to allocate activity costs to each product appropriately based on each activity.